2016
DOI: 10.5114/wiitm.2016.64747
|View full text |Cite
|
Sign up to set email alerts
|

Improving the results of transarterial embolization of type 2 endoleaks with the embolic polymer Onyx.

Abstract: IntroductionType 2 endoleaks (T2E) occur in 10 to 20% of patients after endovascular abdominal aortic aneurysm repair (EVAR) and remain a significant clinical issue.AimTo evaluate the efficacy and clinical outcomes of transarterial treatment of persistent type II endoleaks after EVAR using the liquid embolic Onyx.Material and methodsFrom February 2012 to August 2015 transarterial T2E embolization was attempted in 22 patients (21 men, median age: 73, range: 62–88 years). Indications for treatment included an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…However, the definition of clinical success was not uniform and included the lack of evidence of a residual endoleak and/or the detection of a stable or regressive aneurysm diameter on follow-up CT imaging [24]. Similar clinical success rates for T2EL were also found in later studies with EVOH being used alone or in combination with coils [17,26,27,43]. On a retrospective basis, technically incomplete embolization of T2ELs with EVOH does not necessarily rule out clinical success [26].…”
Section: Technical and Clinical Results Achieved With Evohmentioning
confidence: 97%
“…However, the definition of clinical success was not uniform and included the lack of evidence of a residual endoleak and/or the detection of a stable or regressive aneurysm diameter on follow-up CT imaging [24]. Similar clinical success rates for T2EL were also found in later studies with EVOH being used alone or in combination with coils [17,26,27,43]. On a retrospective basis, technically incomplete embolization of T2ELs with EVOH does not necessarily rule out clinical success [26].…”
Section: Technical and Clinical Results Achieved With Evohmentioning
confidence: 97%
“…Previous case series have presented their institutions experience with Onyx ® with favourable results though with no comparison to other embolic agents and variable follow-up times. [21][22][23][24][25] One study found Onyx ® use to have greater success rates than coil or non-Onyx ® glue treatment. 26 A recent systematic review of evidence for Onyx ® as an embolic agent emphasized the lack of data present and with the largest series reporting a median follow-up time of only 4 months.…”
Section: Discussionmentioning
confidence: 99%
“…Die Ergebnisse der Behandlung des Typ-II-Endoleaks mit transarterieller Embolisation zeigen klinische Erfolgsraten (kein weiteres Wachstum des Aneurysmasacks im Follow-up) zwischen 65 und 100 % [ 24 , 33 , 44 , 58 ].…”
Section: Typ-ii-endoleakunclassified